The application of talent management for the faculty in emerging Saudi universities - Jeddah, Majmaah, Hafr Al-Batin - in the light of international experiences and their point of view - Ruzzah, Olfat Saleh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the degree of application of talent management to faculty members in emerging Saudi universities in the light of international experiences and their obstacles from the viewpoint of faculty members, and the impact of variables (gender, academic rank, years of service, university) on their answers. The study used the descriptive survey method. The questionnaire was used as its tool. It was distributed to a random sample of (326) members of the teaching staff in the universities (Jeddah, Majmaah, Hafr Al-Batin). To analyze the data, a statistical analysis program (SPSS) was used. The results of the study revealed that the application of talent management to faculty members in emerging Saudi universities in the light of international experiences obtained a total average (2.57 out of 5), i.e. with a (low) degree of application. (2.65), both with a degree of application (medium), and thirdly: talent performance management with an average of (2.49) and finally: talent retention with an average of (2.47), both with a degree of application (low).. The results also showed that there are (18) obstacles to the application of talent management, the most important of which is lack of funding. And financial support for talent management in emerging universities. The results also showed that there were no statistically significant differences at the level of significance (α 0.05) between faculty responses due to the variables (gender, years of service, university). Based on the results, the researcher recommended the need to improve the application of talent management for the faculty, and to hold specialized training courses for academic leaders on the application of talent management and its application mechanisms, and to reduce the obstacles that prevent the application of talent management in each university separately, and in all Saudi universities.